IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM PENURUNAN PREVALENSI STUNTING - Wahyuni, Tri; A, Rustan; Sartika, Dewi; Kusumaningrum, Mayahayati; Sari, Maria AP (Jurnal Riset Inossa : Media Hasil Riset Pemerintahan, Ekonomi dan Sumber Daya Alam, 2024)
The demographic bonus is one of the future gifts for Indonesia, because the percentage of the population in productive age is greater than the population in the non-productive age phase. In order for the demographic bonus to be a gift, it is necessary to prepare a superior and qualified future generation to achieve the goal of a golden Indonesia in 20245. One of the major problems that overshadows the quality of Indonesia's demographic bonus is the problem of stunting. Until now, Indonesia still has a bad record regarding stunting rates. Various efforts have been made by the government regarding efforts to reduce stunting prevalence. The stunting prevalence target of 14% in 2024 has yet to be met. On the other hand, the fulfilment of policy products related to regulations has been widely issued, as well as related to budget fulfilment. This research wants to target the issue of the implementation of handling stunting, which still leaves many problems. By using Edward III's implementation theory approach, this research wants to map implementation issues using indicators of communication, resources, disposition, and bureaucratic structure. The method used in this research uses a qualitative approach. Qualitative research is carried out with research techniques that use narratives or words in explaining or describing the meaning of each phenomenon, symptom, and certain social situations. From the results of the analysis carried out, it was found that related to communication indicators, there needs to be good interaction from all stakeholders involved. Related to resources, the role, appreciation and development of cadres needs to be done as the spearhead of services. Disposition indicators. The lack of checks and rechecks on stunting handling programmes and activities is a policy agenda for disposition indicators. As for the bureaucratic structure, TPPS and rembug stunting must be streamlined, not just as ceremonial activities. The conclusion of this research is to optimise the implementation of the substance of Presidential Regulation No. 72 of 2021, especially related to coordinated implementation efforts, sensitive interventions to get attention. Synergy, consistency of activities, and innovation in handling stunting are optimised, and data management that supports the strengthening of stunting data is intensified.